AIR MOISTURE ANALYSIS OF POTATO DEHUMIDIFICATION PROCESS USING THE REFRIGERATION SYSTEM - HIDAYATI, BAITI; ., Baharuddin; Wahyudi, Reza (Politeknik Negeri Sriwijaya, Indonesia, 2020)
The refrigeration system is one of the technologies used to condition thetemperature of the air either by heating or cooling, in general refrigeration iscommonly used for human comfort needs and also for the freezing process. Inthis research, refrigeration is used for the process of drying potatoes using adehumidification method, which is the reduction of moisture in the air vapor.Potatoes will be cooled using a refrigeration process and then will be heatedusing a heater, data collection is carried out at a temperature of 600C heater, withdata collection each of 60 minutes, 120 minutes and 180 minutes. From theresults obtained, the dehumidifier method using a refrigeration system can drypotatoes to shrink 60% and humidity can be reduced to 83.3%.